Diagnostic capability of colon capsule endoscopy for advanced colorectal cancer: A pilot study. Issue 6 (24th April 2017) - Ota, Yumiko; Yamada, Atsuo; Kobayashi, Yuka; Niikura, Ryota; Shimpoh, Takayuki; Narita, Akiko; Yoshida, Shuntaro; Suzuki, Nobumi; Watabe, Hirotsugu; Hirata, Yoshihiro; Ishihara, Soichiro; Sunami, Eiji; et al.
Abstract : Background and Aim: Colon capsule endoscopy (CCE) is a safe and effective method for detecting lesions in the colon. However, the sensitivity of CCE in detecting advanced colorectal cancer (CRC) has not been sufficiently evaluated. Therefore, the aim of the present study was to assess the sensitivity of CCE in detecting advanced CRC. Methods: Patients previously diagnosed with advanced CRC by conventional colonoscopy underwent CCE. Primary outcome measure was the sensitivity of CCE in detecting advanced CRC per patient and per lesion. Secondary parameters measured were the sensitivity of CCE in detecting polyps ≥6 mm and ≥10 mm in size in a per‐lesion analysis and the safety of CCE. Results: Of the 21 advanced CRC lesions in 20 patients, 17 were detected by CCE. The per‐patient and per‐lesion sensitivities of CCE for detecting advanced CRC lesions were 85% (95% confidence interval [CI]: 62–97%) and 81% (95% CI: 58–95%), respectively. All advanced CRC lesions were diagnosed in the accessible region by CCE while the capsule was still functional. A significant association was found between incomplete CCE and failure to diagnose advanced CRC. No severe adverse events occurred. Conclusion: The diagnostic capability of CCE in detecting advanced CRC was limited in cases of procedure incompletion. Refining procedures to increase CCE procedure completion rates are required to enhance CRC detection.